Influence of substrates on the nutritional quality of Pleurotus pulmonarius and Pleurotus ostreatus - T. Garuba (Ceylon Journal of Science, 2017)
This investigation is aimed at determining the influence of agro-wastes as substrates on the nutritional quality of Pleurotus pulmonarius and Pleurotus ostreatus. Cassava peels, banana leaves and amended sawdust (sawdust mixed with rice bran in ratio 4:1) were used as growth substrates. Proximate and mineral analyses were carried out using DA 7250 NIR Analyzer and Atomic Absorption of Spectrophotometer machine (AA320N). Both species in amended sawdust had the highest stipe length and pileus diameter of the fruiting body. Starch was the most abundant proximate constituent in the two species. The starch was the most abundant proximate constituent in the two species but highest starch contents were observed in. P. pulmonarius grown in cassava peels substrate and P. ostreatus raised in banana leaves substrate. Fat appeared to be the lowest proximate constituent in the two species. Potassium was predominant among the minerals in both P. pulmonarius and P. ostreatus and the highest value (68.204 mg/L) was observed in P. ostreatus cultivated in amended sawdust. Other minerals varied considerably and as they were differential affected by the substrates. The mushrooms contained useful nutritional constituents however their quantities were influenced by the substrates used in raising them.